1725 Pa. Laws 31, An Act For The Better Securing Of The City Of Philadelphia From The Danger Of Gunpowder, § 2. - (:unkn) unknown (My University, 1725)
No person whatever within the precincts of the city of Philadelphia aforesaid, nor within Two Miles thereof, shall, from and after the Time the Powder Store aforesaid is so erected and finished presume to keep in any House, Shop, Cellar, Store, or Place of the said City, nor within Two Miles thereof, other than the Powder Store aforesaid, any more or greater Quantity, at any one Time, than Twelve Pounds of Gun-powder, under the Penalty of Ten Pounds for every such Offence.
Keywords: GUNPOWDER - STORAGE